A new model for chronic and reactivation tuberculosis: Infection with genetically attenuated Mycobacterium tuberculosis in mice with polar susceptibility. (December 2018) - Kondratieva, Tatiana K.; Kapina, Marina A.; Rubakova, Elvira I.; Kondratieva, Elena V.; Nikonenko, Boris V.; Majorov, Konstantin B.; Dyatlov, Alexander V.; Linge, Irina A.; Apt, Alexander S.
Abstract: TB infection in mice develops relatively rapidly which interferes with experimental dissection of immune responses and lung pathology features that differ between genetically susceptible and resistant hosts. Earlier we have shown that the M. tuberculosis strain lacking four of five Rpf genes (ΔACDE) is seriously attenuated for growth in vivo . Using this strain, we assessed key parameters of lung pathology, immune and inflammatory responses in chronic and reactivation TB infections in highly susceptible I/St and more resistant B6 mice. ΔACDE mycobacteria progressively multiplied only in I/St lungs, whilst in B6 lung CFU counts decreased with time. Condensed TB foci apeared in B6 lungs at week 4 of infection, whilst in I/St their formation was delayed. At the late phase of infection, in I/St lungs TB foci fused resulting in extensive pneumonia, whereas in B6 lungs pathology was limited to condensed foci. Macrophage and neutrophil populations characteristically differed between I/St and B6 mice at early and late stages of infection: more neutrophils accumulated in I/St and more macrophages in B6 lungs. The expression level of chemokine genes involved in neutrophil influx was higher in I/St compared to B6 lungs. B6 lung cells produced more IFN-γ, IL-6 and IL-11 at the early and late phases of infection. Overall, using a new mouse model of slow TB progression, we demonstrate two important features of ineffective infection control underlined by shifts in lung inflammation: delay in early granuloma formation and fusion of granulomas resulting in consolidated pneumonia late in the infectious course.